Probiotics Isolated From Animals in Northwest China Improve the Intestinal Performance of Mice - Li, Yingying; Jia, Dan; Wang, Jiahui; Li, Hehai; Yin, Xijuan; Liu, Junlong; Wang, Jinming; Guan, Guiquan; Luo, Jianxun; Yin, Hong; Xiao, Sa; Li, Youquan (Frontiers in Veterinary Science, 2021)
Antibiotic-resistance is an increasingly prevalent problem worldwide. Probiotics are live microorganisms that provide health benefits to the human beings and animals，and also antimicrobial activity against pathogens and might be an antibiotics alternative. The gastrointestinal tract of animals can be a suitable source of finding novel antimicrobial agents where the vast majority of gut microbes inhabited and a plurality of antimicrobial producers exhibit either wide or narrow spectrum. Animals lived in Northwest China might possess special commensal community in the gut. Therefore, the purpose of this study was to assess the effects of three probiotics strains (including Lactobacillus salivarius ZLP-4b from swine, Lactobacillus plantarum FBL-3a from beef cattle, and Bacillus velezensis JT3-1 from yak) , which were isolated from livestock in this area, on overall growth performance, immune function and gut microbiota of mice. The results showed that the L. salivarius ZLP-4b group not only improved the growth performance but also amended the intestinal mucosa morphology of mice. Further, the supplementation of L. plantarum FBL-3a and L. salivarius ZLP-4b strains significantly increased the content of anti-inflammatory cytokines IL-4 and IL-10 but decreased pro-inflammatory factor IL-17A. The levels of pro-inflammatory factors, IL-6, IL-17A and TNF-α were also decreased by B. velezensis JT3-1 group pretreatment. The 16S rDNA sequence results showed that the probiotics administration could increase the proportion of Firmicutes/Bacteroidetes of intestinal microbes in mice. Furthermore, the relative abundance of Lactobacillus was boosted in JT3-1 and ZLP-4b-treated group, and that of opportunistic pathogens (including Proteobacteria and Spirochaetes) was diminished in all treated groups compared with the control group. In conclusion, B. velezensis JT3-1 and L. salivarius ZLP-4b supplementation enhanced overall performance, intestinal epithelial mucosal integrity, immune-related cytokines and regulated intestinal microbiota in mice.